2010
DOI: 10.3758/pbr.17.5.630
|View full text |Cite
|
Sign up to set email alerts
|

Prospects behind bars: Analyzing decisions under risk in a prison population

Abstract: Criminal activity often involves considerable risks. It is therefore not surprising that criminals have been speculated to differ from noncriminals in risk attitude. Yet, few data exist to support this assumption. Moreover, the psychological underpinnings of differences in risk attitude are currently little understood. We presented prisoners and controls with sets of risky decision tasks and modeled their responses using cumulative prospect theory (CPT). The two groups showed several differences. Prisoners wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

8
2

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 36 publications
1
45
0
Order By: Relevance
“…Analyses of simple strategies have shown that this is not necessarily the case. For example, a person recognizing many Swiss cities can, if recognition is a good predictor, be less accurate in judging the sizes of Swiss cities than a person recognizing fewer cities – the less-is-more effect (Goldstein and Gigerenzer, 2002; for a review, see Pachur, 2010). The reason is that if many cities are recognized, the recognition heuristic cannot be applied (because recognition does not discriminate) and other, potentially less valid predictors need to be recruited – leading to lower inferential accuracy.…”
Section: Ecological Rationality: the Fit Between Mind And Environmentmentioning
confidence: 99%
“…Analyses of simple strategies have shown that this is not necessarily the case. For example, a person recognizing many Swiss cities can, if recognition is a good predictor, be less accurate in judging the sizes of Swiss cities than a person recognizing fewer cities – the less-is-more effect (Goldstein and Gigerenzer, 2002; for a review, see Pachur, 2010). The reason is that if many cities are recognized, the recognition heuristic cannot be applied (because recognition does not discriminate) and other, potentially less valid predictors need to be recruited – leading to lower inferential accuracy.…”
Section: Ecological Rationality: the Fit Between Mind And Environmentmentioning
confidence: 99%
“…Examining the recognition heuristic analytically, Goldstein and Gigerenzer (2002) showed that a less-is-more effect will emerge in a comparison task if (but not only if) the recognition validity (α) is higher than the knowledge validity (β), under the assumption that the validities are constant across different levels of the number of recognized objects, n (although they showed in computer simulations that the less-is-more effect can also occur when α is not constant). More recently, Pachur (2010) highlighted that the less-is-more effect is strongly reduced if people who recognize more objects also have a higher knowledge validity, that is, if n and the knowledge validity are positively correlated (see also Smithson, 2010). Finally, the less-is-more effect is also influenced by the quality of recognition memory.…”
Section: The Foundations and Implications Of The Recognition Heuristicmentioning
confidence: 99%
“…Willemsen, Böckenholt, & Johnson, 2011). Understanding the cognitive processes, however, is key for predicting and improving behavior (e.g., Payne & Venkatraman, 2011; see also Glöckner & Pachur, 2012;Pachur, Hanoch, & Gummerum, 2010). Toward the goal of developing a more process-oriented account of the endowment effect, it has been speculated that buyers and sellers focus their attention on different aspects of the target object (e.g., Carmon & Ariely, 2000).…”
mentioning
confidence: 99%